Quando começa a pessoa legal? O nascituro no legislativo brasileiro - Potechi, Bruna (2013)
This effort analyzes the possible constructions of nascituru (unborn human) as a person under Brazilian legislation. In May of 2010 was approved, by one committee of the Deputy´s Chamber, the Law´s Project 478 of 2007 providing a Statute of the Nascituru, then we could visualize embryos and fetuses become a person and a subject of rights from a legislative point of view. However, in Brazilian legislation the nascituru could be a person or not be, depending on the case. Meanwhile the Nacituru´s Statute intended to define the nascituru as a subject of rights and become them a legal person, we could see in the law and law´s proposition about abortion and new reproductive technologies the nascituru do not always show up as a person. Hence in some cases is allowed abortion, and also research of embryos in vitro, or even reject them. The Law´s project 478 of 2007 is the first one to treat simultaneously the themes of abortion and new reproduction technologies, deliberating from the perspective of the nascituru. Thus, we observe in this effort the nascituru´s different constructions as a person to the legislation when he is and isn´t a legal person. Following, we understand the different discourses in the Deputy´s Chamber about the moment of life that we can call nascituru, the time before birth. Finally we can observe how the nascituru might be person and non-person, and how he appears as a subject of rights and then how the rights of the different subjects are in relation and how this subjects could be more or less legal person to Brazilian law.